Dynamic triggering: The effects of remote earthquakes on volcanoes, hydrothermal systems and tectonics - Fuchs, Florian (Universitäts- und Landesbibliothek Bonn, 2015)
Dynamic stresses induced by seismic waves from large earthquakes can trigger a variety of geologic phenomena. This thesis focuses on observational evidence of dynamically triggered seismic activity in hydrothermal, volcanic and mud-volcanic systems. During summer 2011 and 2013 we discovered microseismic activity under the Snæfellsjökull volcano, Iceland. Earthquakes with magnitudes Ml < 1.5 are located around 5–13 km below sea level. Seismicity likely reflects hybrid events that involve brittle failure in combination with fluid-related processes in deep sections of the crust. Additional Synthetic Aperture Radar Interferometry shows no vertical surface deformation between years 2004 and 2008, indicating negligible inflation/deflation within the inferred magma reservoir. We analyze the triggering of seismic activity at the Irazú-Turrialba volcanic complex, Costa Rica, following the 2012 Mw 7.6 Nicoya earthquake. After the passage of seismic waves we observe a sudden increase in seismicity lasting approximately 36 hours with a maximum rate of 75 events/hour. We point out that Mw < 4.5 aftershocks are also followed by increased seismicity. We propose the combined action of dynamic stress and short-lived coseismic relaxation triggered seismic activity in this near-critical system. Additionally, we show similar earthquake triggering by teleseismic surface waves in the Larderello-Travale geothermal field, Italy. Furthermore, we present evidence for triggered tremor beneath the island of Sumbawa, Indonesia. We show tremor in response to three teleseismic earthquakes and constrain a triggering threshold of 8 kPa dynamic stress. Triggered tremor amplitudes scale with induced ground velocity. Tremor responds to 45–65 s period surface waves and predominantly correlates with Rayleigh waves. We could not locate the tremor but data indicates potential source volumes such as the Flores Thrust, the Java subduction zone, or Tambora volcano. Using numerical wave propagation we investigate the trigger of the 2006 Lusi mud ...